Evaluating the Economics Education Framework Within the Merdeka Curriculum at the Ecd Level: Case Study at Kharisma Kindergarten - Nuraini, Fariha; Sholikhah, Annisa Mar’atus; Wahjoedi; Rahmawati, Farida; Tahir, Aisha (Indonesian Scientific Publication, 2024)
Education is of paramount importance in shaping a nation's character. This is particularly relevant in Indonesia, where the President of Indonesia has prioritized the Merdeka Curriculum across all levels of education. This curriculum is being implemented at the early childhood education (ECD) level following government policy guidelines in Permendikbud ristek Number 5/2022. This research uses a qualitative case study research method with the CIPP evaluation model at Kharisma Kindergarten Malang to investigate the evaluation of the implementation of economic learning in the Merdeka Curriculum in ECD education. The study employed purposive sampling to select Kharisma Kindergarten Teachers in Malang, School Supervisors in Malang Regency, and the Head of the Early Childhood Education Section in Malang Regency. The results of qualitative research using the triangulation method show that the Merdeka Curriculum has been implemented 90% at the kindergarten level. In detail, the results of interviews with the head of curriculum at Kharisma Kindergarten show that the Merdeka Curriculum was implemented at school 100% in 2024. However, the researchers identified obstacles regarding teacher and parent paradigms and limited facilities, which prevented the curriculum from being successfully implemented. Therefore, teachers, parents, and students need to accept new teaching methods and ideas if the Merdeka Curriculum is to work well in ECD education.